PENGARUH HARAPAN PELANGGAN, KUALITAS PRODUK, KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi Kasus Depo Bangunan PT Barokah Tunas Muda Surabaya) - Ahmad Suja’i; Muhammad Mansur; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT Customers are an important part of the business world, without any customers in the business, of course there will be no business processes that occur. Therefore customers are very influential in the wheels of business and business. This study aims to explain the effect of customer expectations, product quality, customer satisfaction on customer loyalty. In this study the Customer is an important part of the business world, without any customers in the business, of course there will be no business processes that occur. Therefore customers are very influential in the wheels of business and business. In a business process, the customer would want to be well served by the merchant and the customer will be satisfied if his wishes or expectations are met when buying and feeling the product or service that is felt. With such an impact, it is expected that customers will be loyal to use the product or service that they feel is good. The purpose of this study was to determine the effect of service quality and customer satisfaction on customer loyalty. The method used is quantitative. The method of data analysis in this study was to use descriptive statistical methods and parametric inferential statistics by using IBM Version 21 SPSS (statistical product and service solution) software. The results showed that the coefficient of determination obtained service quality to customer loyalty was 3.84% while the effect of customer satisfaction on customer loyalty is 3.74% and the effect simultaneously between service quality and customer satisfaction on customer loyalty is 3.64% and the remaining 3.38% is influenced by other variables not examined in this study. Keywords: service quality, customer satisfaction, customer loyalty